The Personality of the Scribe and Communal Book Collections in the Old Belief: Monk Cyprian and the Library of the Skete on Ilyushkin Island - Melnikov, Ilya (Slavistica Vilnensis, 2021)
The article is devoted to the problem of the relation of personal and communal libraries in the Old Believers communities on the example of the book collection of a skete on Ilyushkin Island of the Novgorod district, an inventory of which was found in the funds of the Novgorod Museum-Reserve. The initiator of the revival of the skete at the end of 19th century monk Cyprian (Sozonov) was directly involved in the formation of this library. His personal views and passions found expression in the selection of skete books. This becomes especially obvious thanks to the comparison of the description of the book collection with the composition of the author’s miscellany, which was written by the sket superior, as well as the newly revealed documents covering his activities. In a sense, the library of the monastery can be considered an expression of a full-fledged cultural program, predetermined by the religious views of Cyprian. In its basis, in addition to the characteristic traditional orientation towards worship and monastic activity, it also reveals a polemical attitude and historicism. In addition to the sources related to the bookishness of the skete on Ilyushkin Island, documents are introduced into the scientific circulation, covering its history and the socio-cultural context in which the analyzed book collection of the skete was formed.